2018
DOI: 10.4062/biomolther.2017.113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Choline Transporter-Like Proteins in Esophageal Cancer Cells and Potential Therapeutic Targets

Abstract: In this study, we examined the molecular and functional characterization of choline uptake in the human esophageal cancer cells. In addition, we examined the influence of various drugs on the transport of [3H]choline, and explored the possible correlation between the inhibition of choline uptake and apoptotic cell death. We found that both choline transporter-like protein 1 (CTL1) and CTL2 mRNAs and proteins were highly expressed in esophageal cancer cell lines (KYSE series). CTL1 and CTL2 were located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Similar to the high-affinity choline transporter CHT1, CTL1 is selectively inhibited by the choline analogue hemicholinium-3 (CH-3), yet with a much lower sensitivity. In recent years, further choline uptake studies confirmed the expression and choline transporter function of CTL1/SLC44A1 in human lung alveolar cells, 28 mouse bone marrow-derived macrophages, 42 rat renal tubule epithelial cells, 30 human keratinocytes, 31 human brain microvascular endothelial cells, 14 rheumatoid arthritis synovial fibroblasts, 40 mouse muscle and liver cell lines, 32,33 and numerous cancer cell lines 26,28,[34][35][36][37][38][39]41 as summarized in Table 1.…”
Section: Slc44a Proteinsmentioning
confidence: 77%
See 3 more Smart Citations
“…Similar to the high-affinity choline transporter CHT1, CTL1 is selectively inhibited by the choline analogue hemicholinium-3 (CH-3), yet with a much lower sensitivity. In recent years, further choline uptake studies confirmed the expression and choline transporter function of CTL1/SLC44A1 in human lung alveolar cells, 28 mouse bone marrow-derived macrophages, 42 rat renal tubule epithelial cells, 30 human keratinocytes, 31 human brain microvascular endothelial cells, 14 rheumatoid arthritis synovial fibroblasts, 40 mouse muscle and liver cell lines, 32,33 and numerous cancer cell lines 26,28,[34][35][36][37][38][39]41 as summarized in Table 1.…”
Section: Slc44a Proteinsmentioning
confidence: 77%
“…In choline-deficient skin fibroblast from the postural orthostatic tachycardia syndrome (POTS) patient mentioned above, CTL1/SLC44A1 protein is reduced, and at the same time, oxygen consumption, mitochondrial potential, and glycolytic activity are diminished and mitochondrial function therefore impaired. 43 Recent studies could also localize CTL2/SLC44A2 protein to the mitochondria of human esophageal cells, 41 renal tubule epithelial cells, 30 human tongue carcinoma cells, 39 and human brain microvascular epithelial cells. 14 The purpose of a widely expressed choline transporter in the mitochondrial membrane is not clear yet, but it is likely that there is a link between CTL1/SLC44A1-mediated choline transport and mitochondrial phospholipid metabolism.…”
Section: Mitochondrial Choline Transportersmentioning
confidence: 99%
See 2 more Smart Citations
“…These results do not support the theory that ocTs play a predominant role in choline transportation in Fa2n-4 cells. To date, it has been suggested that a cTl1-mediated choline uptake system functions in primary human tumor cell cultures, such as colon carcinoma cells (19), keratinocytes (20), esophageal cancer cells (21), small cell lung carcinoma cells (22), tongue cancer cells (13), and trophoblastic cells (23). likewise, cTl1 is ubiquitously expressed in mammalian tissues, suggesting an important role in choline transportation.…”
Section: Discussionmentioning
confidence: 99%